Current Status and Threats to Fishing Cat Prionailurus viverrinus (Bennett, 1833) in Godavari Mangroves, Andhra Pradesh, India - Sathiyaselvam, P; Satyanarayana, Eswar; Kathula, Tarun (Indian Forester, 2016)
Godavari Mangroves the second largest patch along the east coast of India with an extend of 33,263.32 ha. are located in Godavari Estuary of East Godavari District, Andhra Pradesh. Coringa Wildlife Sanctuary is the part of Godavari Mangroves, which supports many unique flora and fauna including the globally threatened fishing cat. A comprehensive study was conducted to assess the current status and threats to the fishing cat in Coringa Wildlife Sanctuary through camera trapping, questionnaire surveys, direct sighting and indirect sign surveys. Totally 257 images of fishing cat were captured and 73 individuals were identified. The estimated population of fishing cat in Coringa Wildlife Sanctuary was 95-100 and estimated density was 0.7 animals/km2 or 32 animals/4 km .Fish and field rats were the preferred food for the fishing cats. It was mostly nocturnal as 74% the captures were during night times. The captured images also showed that the fishing cats followed the same tracks. Human animal conflicts were recorded and the conflict zones within the sanctuary were mapped. The existed human-fishing cat conflicts could be categorized into five different types viz. conflict between fishing cat and fishermen, aqua farmers, villagers, encounters during developmental activities and others like road kills, target killing, etc., Awareness programmes, radio-telemetry studies, responsible gap plantation and habitat restoration were recommended for conservation and management of the fishing cats in Coringa Wildlife Sanctuary.